latrogenic Pneumothorax Caused by Thoracic Puncture Secondary to Anti-aging Medicine - Martinez-Rodriguez, Yamile; Rodriguez-Diaz, Zobeida; Tellez-Quijada, Fernanda; Sanchez-Melo, Brenda; Buendia-Roldan, Ivette (Archives of Case Reports, 2023)
Introduction: Pneumothorax is defined as air in the pleural cavity, the iatrogenic cause happens after invasive procedures as thoracic needle aspiration, central line placement, pacemaker placement, etc. Nevertheless, it is possible to be found in non-medical procedures, such as alternative medicine, more specifically acupuncture. There are medications used against aging that FDA has warned to be used only in its first objective, an example is procaine hydrochloride. Case: A 63 y/o female, Mexico City resident, with anxiety, came to a follow-up appointment for an aging cohort, where CT, PFT, and laboratories are made for pulmonary healthy subjects to investigate normal lung aging and how other environmental factors can affect the lungs; at physical examination, we did not find any pleuropulmonary syndrome, but in the CT a left Iatrogenic pneumothorax was found; we re-asked for antecedents and she described that 15 days before the date she had 2 punctures in the middle clavicular line to apply procaine hydrochloride as an anti-aging treatment. Discussion: There is diverse evidence of adverse effects associated with acupuncture, and even if pneumothorax has a small percentage of incidence, in some cases it can be severe and can even cause fatalities. Conclusion: The pneumothorax in this case was iatrogenic due to the thoracic puncture for an anti-aging treatment, with a total resolution with conservative treatment, however we as health professionals have the responsibility to inform our patients that initiatives of administration ways can cause important complications.